Genetic Polymorphism of LBX1 Is Associated With Adolescent Idiopathic Scoliosis in Northern Chinese Han Population. Issue 15 (1st August 2017) - Liu, Sen; Wu, Nan; Zuo, Yuzhi; Zhou, Yangzhong; Liu, Jiaqi; Liu, Zhenlei; Chen, Weisheng; Liu, Gang; Chen, Yixin; Chen, Jia; Lin, Mao; Zhao, Yanxue; et al.
Abstract : Study Design: A case-control association study was performed to investigate the relationship between ladybird homeobox ( LBX1 ) and adolescent idiopathic scoliosis (AIS) in northern Chinese Han population. Objective: To explore the prevalence and functional importance of LBX1 polymorphisms in patients with AIS within the northern Chinese Han population. Summary of Background Data: AIS is the most common subtype of idiopathic scoliosis. Genetic factors such as LBX1 polymorphisms have been recently proved to be associated with AIS in some populations. In this study we explored the prevalence and functional importance of the polymorphisms around LBX1 in patients with AIS within the northern Chinese Han population. Methods: Five tag single nucleotide polymorphisms (SNPs) around or in LBX1 were genotyped in 180 patients with AIS and 182 controls. And the luciferase assay was performed to explore the functional importance of the most significant SNPs. Results: We replicated that rs11190870, previously reported as the most significantly associated SNP, was enriched in our AIS cohort. In addition, we found that the T allele of rs1322331 was associated with a novel risk allele (odds ratio = 3.349, 95% confidence interval 1.742–6.436). In the following luciferase assay, the TT-type promoter showed significantly reduced transcription activity in vitro . Conclusion: Two SNPs around LBX1, rs11190870 and rs1322331 are associated with AIS in northern Chinese Han population. The T allele of rs1322331 is a novel risk allele. We hypothesize that rs1322331 might increase patients' susceptibility to AIS by reducing LBX1-AS1 transcription and thus upregulating the function of LBX1 . Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the text